Calorie and Protein Consumption Pattern Among Desert People of Rajasthan During Drought - Krishnamachari, K A.V.R; Laxshminarayan, J; Rajlakshmi, K; Ganguly, K K; Sheshpal, Sheshpal; Dixit, A K; Mahapatra, A; Dam, P K; Chand, Ramesh; Pandey, R M (Annals of Arid Zone, 2016)
A two point sUiveyofthe Cereal (millet) consumption pattern of selected rural families residing in six desert districts of Rajasthan, viz., Jodhpur, Jalore, Nagaur, Sikar, Jaisalmer and Barmer was carried out during the drought years of 1987 and 1988. Two thousand persons representing each dist : tand drawn from ten villages were examined with regard to their milet consumption pattern. In a sub-sample of 800persons drawn from ten villages in each district from five of the former six districts. Similar information was obtained during the second point of he study. The mean calorie intakes were ranging from 301 to 982 kcals per day in preschool children. Accordingly the deficit was more than 50% in all the districts except in Jodhpur district. Sirrilarly among 5-15 years age group in both the sexes the deficits were observed to be ranging from 31.9% to 68.5%. The deficits ranging from 11.9% to 57.0% among 15-45years age group, however in all the districts except in Jodhpur and Jalore the intakes were lower as compared to ICMR recommended dietary allowances. Protein deficiency were seen in all the age groups in all the districts but were relatively less as compared to corresponding calorie intake. The body weights and calorie consumption were observed to be comparable among districts as well as among different physiological groups. However calorie deficits (> =35%) was relatively more in Barmer district as compared to other districts. The mean body weight and actual calorie consumption were observed to be around 46 Kg and 2400 Kcals. respectively.